Inverse Modulation of Neuronal Kv12.1 and Kv11.1 Channels by 4-Aminopyridine and NS1643 - Dierich, Marlen; Evers, Saskia; Wilke, Bettina U.; Leitner, Michael G. (Frontiers in Molecular Neuroscience, 2018)
The three members of the ether-à-go-go-gene-like (Elk; Kv12.1-Kv12.3) family of voltage-gated K+ channels are predominantly expressed in neurons, but only little information is available on their physiological relevance. It was shown that Kv12.2 channel modulate excitability of hippocampal neurons, but no native current could be attributed to Kv12.1 and Kv12.3 subunits yet. This may appear somewhat surprising, given high expression of their mRNA transcripts in several brain areas. Native Kv12 currents may have been overlooked so far due to limited knowledge on their biophysical properties and lack of specific pharmacology. Except for Kv12.2, appropriate genetically modified mouse models have not been described; therefore, identification of Kv12-mediated currents in native cell types must rely on characterization of unique properties of the channels. We focused on recombinant human Kv12.1 to identify distinct properties of these channels. We found that Kv12.1 channels exhibited significant mode shift of activation, i.e. stabilization of the voltage sensor domain in a “relaxed” open state after prolonged channel activation. This mode shift manifested by a slowing of deactivation and, most prominently, a significant shift of voltage dependence to hyperpolarized potentials. In contrast to related Kv11.1, mode shift was not sensitive to extracellular Na+, which allowed for discrimination between these isoforms. Sensitivity of Kv12.1 and Kv11.1 to the broad-spectrum K+ antagonist 4-aminopyridine was similar. However, 4-AP strongly activated Kv12.1 channels with an EC50 of about 3.1 mM and a Hill coefficient of 0.9, but it was an inhibitor of Kv11 channels (EC50 approx. 2.6 mM; Hill coefficient 0.7). Interestingly, the agonist of Kv11 channels NS1643 also differentially modulated the activity of these channels, i.e. NS1643 activated Kv11.1, but strongly inhibited Kv12.1 channels. Thus, these closely related channels are distinguished by inverse pharmacological profiles. We identified unique biophysical and pharmacological properties of Kv12.1 channels and established straightforward experimental protocols to characterize Kv12.1-mediated currents. Identification of currents in native cell types with mode shift that are activated through 4-AP and inhibited by NS1643 can provide strong evidence for contribution of Kv12.1 to whole cell currents.